Polyphenoloxidase activity in peaches after vibration - Dantas, Tiago B. H.; Ferraz, Antônio C. de O.; Honório, Sylvio L.; Lima, Giuseppina P.P. [UNESP] (My University, 2013)
The vibration during transportation is one of the main causes of fruit damage. The actual methodologies used for damage evaluation in fruits seem to be subjective, since most of them are based on visual evaluation. In this study the effect of vibration, for one and two hours, on polyphenoloxidase (PPO) activity in peach pulp was investigated. The relation among PPO activity variation, postharvest time and resting time were also considered. Results showed that vibration affects PPO activity. However, it was not possible to correlate PPO activity variation and vibration.
Keywords: Damage; Peach; Polyphenoloxidase; Vibration